The Effect of Location, Product Quality, and Perceived Price in Increasing Purchase Decision through Brand Image as the Mediator - Hastuti, Tri; Silitonga, Parlagutan (Business Management Journal, 2025)
The purpose of this research is to assess the impact of location, product quality, and price perception on purchasing decisions with brand image as a mediating variable at Tom Sushi. The population that the focus of this study is the visitors Tom Sushi selected as a source of relevant data. The study took a total sample of 260 individuals, using an accidental sampling approach as a selection methodology. Analytical approach utilizing PLS-SEM through SmartPLS 3.0 program. The findings show that location positively influences purchasing decisions and brand image. In addition, product quality also has a positive impact on purchasing decisions and brand image. On the other hand, price perception also has a positive influence on purchasing decisions and brand image. Although brand image does not have a positive and significant impact on purchasing decisions, it is recommended that brand image be used as a variable antecedent to purchasing decisions in subsequent studies.